Opening the Bible : selected writings of Antony Campbell SJ - Campbell, Antony F. (ATF Theology, 2014)
""When Tony Campbell, aged 75, asked the Council of Jesuit Theological College for Emeritus status and retirement from JTC, both were granted most graciously, along with a testimonial document which said in part: 'His teaching has combined evocation and provocation in the best sense of those terms. He has mentored research students with scholarly exactitude and personal care. He has published books of the highest scholarly quality, of engaging readability, and of passionate conviction.'When we at ATF were considering asking him for a volume of Collected Works or Selected Writings, we were well.